2001
DOI: 10.2170/jjphysiol.51.613
|View full text |Cite
|
Sign up to set email alerts
|

Optical Recording of Spontaneous Respiratory Neuron Activity in the Rat Brain Stem.

Abstract: The optical recording method using voltage-sensitive dye is one of the powerful techniques for two-dimensional detection of mass neuronal activity in the brain and for the analysis of spatiotemporal properties [1][2][3][4]. Respiratory neuron activity in the lower brain stem consists of widely extending neuron networks, including respiratory neurons in the ventrolateral medulla (VLM) [5][6][7][8][9][10]. Therefore the optical recordings could also be a very effective method for a spatiotemporal analysis of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…For representation of the time course of fluorescence changes, averaged fluorescence intensity was assessed and inverted in a 50-pixel region of interest covering an area of 92 × 108µm. As discussed before, optical signals presumably reflect primarily the depolarization associated with respiratory drive potentials [35,61].…”
Section: Voltage-sensitive Dye-imagingmentioning
confidence: 82%
“…For representation of the time course of fluorescence changes, averaged fluorescence intensity was assessed and inverted in a 50-pixel region of interest covering an area of 92 × 108µm. As discussed before, optical signals presumably reflect primarily the depolarization associated with respiratory drive potentials [35,61].…”
Section: Voltage-sensitive Dye-imagingmentioning
confidence: 82%
“…2003; Tokumasu et al, 2001; Janczewski et al, 2002), has not been well characterized with respect to exact neurotransmitter phenotype, greatly limiting comparison between studies or conducting specific studies with an identified cell type. Although Onimaru and colleagues have evidence for both inhibitory (Arata et al, 1998) and excitatory-type neurons (Janczewski et al, 2002; Onimaru et al, 2006) in this area, they have provided only correlative physiological data rather than direct recording and histochemical identification of pFRG neurons.…”
Section: Brainstem Respiratory Areas With Identified Major Ionotromentioning
confidence: 99%
“…A recent study provides evidence that pacemaker activity is exclusively associated with gasping patterns in situ (27). The current hypotheses regarding respiratory rhythm generation are largely based on electrophysiological studies, which yield excellent temporal resolution of single-cell activities, but analysis of population activity is difficult.With the recent advances in imaging techniques, the PBC, as well as other respiratory centers, have been studied optically using voltage-sensitive dyes in isolated brain stem-spinal cord preparations (8,23,25,39) and even in the perfused brainstem preparation (9, 29). However, respiratory network functions and the activity of several network elements could not be probed at single-cell resolution.…”
mentioning
confidence: 99%
“…With the recent advances in imaging techniques, the PBC, as well as other respiratory centers, have been studied optically using voltage-sensitive dyes in isolated brain stem-spinal cord preparations (8,23,25,39) and even in the perfused brainstem preparation (9, 29). However, respiratory network functions and the activity of several network elements could not be probed at single-cell resolution.…”
mentioning
confidence: 99%